Libyan Collections in Foreign Herbaria - Farag El-Mokasabi; Naser Omar; Ebtesam El-Garary (AlQalam Journal of Medical and Applied Sciences, 2025)
The objectives of the study were to confine specimens that were deposited in foreign herbaria. The study showed there are thousands of specimens collected from all over Libya by researchers and herbalists who studied the Libyan flora in the past centuries. The largest number of specimens was found in Italian herbaria, and in some European herbaria such as Herbarium Centrale Italicum and Webb Herbarium, Italy (FI), Padua Herbarium, Italy (PAD), British Museum (BM), Herbarium specimens of Université de Montpellier (MPU), Kew, Herbarium Porticense, Italy (PORUN), The Orazio Comes Botanical Museum at the Facoltà di Agraria dell’Università Federico II di Napoli (NAP), University of Jena, Herbarium Haussknecht, Germany (JE), Zurich herbarium (Z), and the Natural History Museum, Vienna – Herbarium, Austria (W), which was represented by one specimen for each. The study found that 56 typification specimens and around 50 plant specimens that are considered endemic in Libya were deposited in foreign herbaria. An annotated checklist of typification specimens, including accepted names, place of collection, collector, and herbarium where they were deposited, was included in this study. As such, it is proposed that further taxonomic revisions be conducted for each taxon. هدفت الدراسة إلى حصر العينات التي تم إيداعها في معشبات خارج القطر الليبي. وقد أظهرت الدراسة أن آلاف العينات تم جمعها من جميع أنحاء ليبيا من قبل الباحثين والعشابين الذين درسوا النباتات الليبية في القرون الماضية. وقد تم العثور على أكبر عدد من العينات في المعشبات الإيطالية، و كذلك في بعض المعشبات الأوروبية مثل معشبة بادوا، ايطاليا، والمتحف البريطاني، وعينات معشبة جامعة مونبلييه، فرنسا، معشبة المتحف الوطني للتاريخ الطبيعي – باريس، فرنسا و الحدائق النباتية الملكية في كيو، بريطانيا، ومعشبة بورتيسنس، ايطاليا و متحف أورازيو كوميس النباتي في كلية الزراعة بجامعة فيديريكو الثاني في نابولي، ايطاليا وجامعة يينا، ومعشبة هاوسكنخت، المانيا، ومعشبة زيورخ، سويسرا، ومتحف التاريخ الطبيعي، فيينا – المعشبة، النمسا، والتي تم تمثيلها بعينة واحدة لكل منها. ووجدت الدراسة أن 56 عينة طرازية وحوالي 50 عينة نباتية تعتبر متوطنة في ليبيا تم إيداعها في معشبات أجنبية. وقد تم تضمين قائمة مرجعية موضحة لعينات التصنيف، بما في ذلك الأسماء المقبولة، ومكان الجمع، والجامع، والمعشبة التي تم إيداعها فيها، في هذه الدراسة. وبناء على ذلك، يقترح إجراء المزيد من المراجعات التصنيفية لكل تصنيف